Odpowiedzi

2010-03-29T17:09:11+02:00
A). 2a-4b-5c-6a-9=-4a-4b-5c-9
b). 4a-2b+3-3a+6b-9=a+4b-6
d). -4a+5b-7-2a-3b+3=-6a+2b-4
e). 3x+5y-4x+6y-7x-9y=-8x+2y
f). -5+2y-4x+5y+6x-3y=-5+4y+2x
g). -2x+3y+3-2y-3x-4+y-4x+2=-9x+2y+1
h). x-2y-4-2x-5+y-3+2x-6y= x-7y-12


pozdrawiam ;**
2010-03-29T17:10:18+02:00
A). 2a-4b-5c-6a-9= -4a-4b-5c-9
b). 4a-2b+3-3a+6b-9= a+4b-6
d). -4a+5b-7-2a-3b+3=-6a+2b-4
e). 3x+5y-4x+6y-7x-9y= -8x+2y
f). -5+2y-4x+5y+6x-3y= 2x+4y-5
g). -2x+3y+3-2y-3x-4+y-4x+2= -9x+2y+1
h). x-2y-4-2x-5+y-3+2x-6y= x-7y-12
2010-03-29T17:11:03+02:00
A=-4a-4b-5c-9
b=-1a+4b-6
c=-6a+8b-4
d=-8a-2y
e=-5+4y+2x
f=-9x+2y-1
g=3x-7y-12